Wiley 5G Ref 2020
DOI: 10.1002/9781119471509.w5gref223
|View full text |Cite
|
Sign up to set email alerts
|

SDN‐Based Session and Mobility Management in5GNetworks

Abstract: The analysis performed in this article is a concise proposal on how SDN solutions can be integrated into 5G mobile networks in order to address key cellular network challenges related to session and mobility management. Initially, we present the key characteristics of SDN and how session and mobility management are performed in this type of networks. Then we present how session and mobility management are performed in 5G mobile networks and what are the potential drawbacks of the conventional designs that coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
6
0
2
Order By: Relevance
“…The authors considered a fixed terminal LTE setup and discussed security issues around trusted domainbased and IPsec VPN-based backhaul architectures. Kaloxylos et al [21] focused on the session and mobility management in SDN-enabled 5G networks. The authors explored the 5G security functions of the 3GPP and suggested the methodologies for including SDN in 5G to increase the performance in the densification of the network.…”
Section: Related Workmentioning
confidence: 99%
“…The authors considered a fixed terminal LTE setup and discussed security issues around trusted domainbased and IPsec VPN-based backhaul architectures. Kaloxylos et al [21] focused on the session and mobility management in SDN-enabled 5G networks. The authors explored the 5G security functions of the 3GPP and suggested the methodologies for including SDN in 5G to increase the performance in the densification of the network.…”
Section: Related Workmentioning
confidence: 99%
“…To discover an idle MN's current location, the location area's cells are contacted through paging. With the upcoming densification of 5G, it is expected that there will be a considerable increase in location management signaling costs due to the increase in location updates (if the tracking areas are small) or paging (if the tracking areas are large) [35].…”
Section: Overview Of Ip-based Standardized Location Management and It...mentioning
confidence: 99%
“…In the lookup process, if the packet header matches a record in the lookup table, then the predefined actions are performed. If the match is not found in the flow table entries then the packet will be forwarded to the controller through the southbound interface [35]. For more details on SDNs, the interested reader may refer to [77].…”
Section: Approach #3: Sdn-based Locationmentioning
confidence: 99%
“…To discover an idle terminal current location, the location area's cells are contacted through paging. With the upcoming densification of 5G, it is expected to encounter a considerable increase in the location management signaling cost due to more location updates (if the tracking areas are small) or paging (if the tracking areas are large) [31].…”
Section: Overview Of Ip-based Standardized Location Management and It...mentioning
confidence: 99%
“…In the lookup process, if the packet headers match can be found in the lookup table, then the predefined actions are performed. If the match was not found in the flow table entries then the packet will be forwarded to the controller through the southbound interface [31]. For more details on SDN, the interested reader may refer to [72].…”
Section: Approach #3: Sdn-based Location Management In Leo Satnetsmentioning
confidence: 99%